SURGICAL TECHNIQUES TO INCREASE RESECTABILITY IN LIVER METASTASIS - Orlando Jorge Martins Torres; Guido Torzilli; Marcelo Enne; Rinaldo Gonçalves; Eduardo de Santibanes; Timothy Pawlik; Rene Adam; Olivier Soubrane; Paulo Herman; Ricardo Lemos Cotta-Pereira (ABCD: Arquivos Brasileiros de Cirurgia Digestiva)
ABSTRACT The development of surgical techniques, chemotherapy, biological agents, and multidisciplinary approaches have made patients with unresectable colorectal liver metastases eligible for surgery. Many strategies have been developed to allow patients for surgical resection (percutaneous portal vein embolization, liver venous deprivation, parenchyma-sparing liver surgery, reverse strategy, associating liver partition and portal vein ligation for staged hepatectomy, and liver transplantation), the only form of disease control and curative treatment.